2019
DOI: 10.1097/aln.0000000000002759
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Childbirth Outcomes Using Administrative and Birth Certificate Data

Abstract: I n the 15 yr since the publication of the Institute of Medicine report highlighting the need to reduce medical errors and improve patient safety, 1 complications after childbirth have become more common, not less common. 2,3 The number of pregnancy-related deaths in the United States increased from 7.2 to 17.3 per 100,000 between 1987 and 2013. 4 Many pregnancy-related deaths, such as those due to hemorrhage and preeclampsia, are preventable 5,6 and the quality of obstetrical care across U.S. hospitals is une… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…For institution effects, we compared predicted nonadherence rates (i.e., institution‐specific or predicted) using both random institution effect and the fixed effect regression estimates to the fixed effects only (population‐average or expected) rates. The intra‐institution comparison of the two rates was used as a measure of institution performance in rates of incremental dosing in excess of the published typical range 37,38 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For institution effects, we compared predicted nonadherence rates (i.e., institution‐specific or predicted) using both random institution effect and the fixed effect regression estimates to the fixed effects only (population‐average or expected) rates. The intra‐institution comparison of the two rates was used as a measure of institution performance in rates of incremental dosing in excess of the published typical range 37,38 …”
Section: Methodsmentioning
confidence: 99%
“…The intra-institution comparison of the two rates was used as a measure of institution performance in rates of incremental dosing in excess of the published typical range. 37,38…”
Section: Institution-specific Propofol Dosing Rates In Excess Of Fda'...mentioning
confidence: 99%
“…In addition, the protective processes and septic procedures might be more stringent at university medical centers, which could be used to explain the result, as there was no difference in the use of prophylactic antibiotics at different hospitals or clinic-based CS performance in Taiwan. Large variations regarding the level of service and the probability of complications across US hospitals have been reported [ 57 ]. Regarding the size of medical units carrying out CSs, the findings from a Canadian study indicated that rural hospitals had lower odds of surgical errors and complications, whereas hospitals with high bed numbers had greater odds of errors and complications than medium bed number hospitals [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…2 The public is skeptical, and now reporters are interviewing women who have suffered irreparable harm and families of those who have died to reveal the extent to which the adverse outcomes reflect failures in clinical care. 2,4 To address this crisis in public accountability, Glance et al 5 have constructed the first composite measure that integrates risk-adjusted maternal and neonatal morbidity and mortality. Their contribution is presented as the foundation of a suite of measurements that women and families could use to select their hospital for delivery and that government and private payers may use to ensure safety, equity, and value.…”
mentioning
confidence: 99%